La práctica controlada de integración para mejorar la habilidad de hablar de los estudiantes de tercer año "a" de bachillerato sección vespertina, en el colegio Rafael rodríguez palacios en la parroquia Malacates de la ciudad de Loja durante el año lectivo 2018- 2019 - Chimbo Vicente, Eufemia Catalina (2019)
The main objective of the research was to improve speaking skill using the Controlled Practice Interaction among students of third year “A” of Bachillerato. To develop this research the methods used were: scientific, descriptive, syntheticanalytical and statistical that allowed to study, to describe, to make quantitative and qualitative analysis and interpreted the results gathered to draw conclusions. The instruments used for data collection were: tests, questionnaires, observation sheets and field notes which helped to diagnose the student’s speaking skills and perception, to determine what has happened in the class and to record what happened in each lesson that were applied to twenty two students. The results showed that students improved considerably their speaking skills in the four aspects comprehension, pronunciation, accuracy and fluency. In conclusion, the use of Controlled Practice Interaction was effective. Students felt more confident and had a positive attitude when they spoke in English language.